Relationship between Brand Awareness and Competitive Advantage of Independent Petroleum Dealers in Uasin Gishu County, Kenya - Kibet Boinett, Collins; Kibet, Yusuf; Jemaiyo, Beatrice (British Journal of Marketing Studies, 2022)
Consumers’ value for a brand is known as "brand equity," and it is expressed in characteristics such as brand recognition, brand associations, perceived quality, brand loyalty, and other exclusive brand assets. The study’s goal was to ascertain the connection between independent petroleum dealers’ brand equity and competitive advantage in Uasin Gishu County, Kenya. This paper examines the relationship between brand awareness and competitive advantage of independent petroleum dealers in Uasin Gishu County, Kenya. The brand equity theory grounded the study. The research design was correlational. A stratified and simple random sampling procedure was used to choose 26 independent petroleum dealers from the target population, consisting of 28 independent petroleum dealers, and a sample size of 338 employees. The questionnaire was chosen as the method for gathering data. The collected data was analysed using descriptive and inferential statistics. The analysis and presentation of descriptive statistics took the form of frequencies, percentages, means, and standard deviation. With the use of multiple regression analysis, the hypotheses were tested. From the study findings, majority of workers concurred, according to the study’s findings, that branding had improved the gas station’s visibility and raised its competitive edge. Additionally, majority of workers believed that strong branding had affected customers’ buying decisions. Similarly, most of the customers found the petroleum brands easy to memorize. They also agreed that branding petroleum dealers would increase brand recognition of the gas station. The study found a significant and positive correlation between independent petroleum dealers’ competitive advantage and brand awareness (p = 0.000). The study recommends that brand endorsement be given more weight in order to strengthen the competitive advantage of independent gasoline dealers in Uasin Gishu County.